2014
DOI: 10.4103/2279-042x.137076
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a local-drug delivery gel containing extracts of Quercus brantii and Coriandrum sativum as an adjunct to scaling and root planing in moderate chronic periodontitis patients

Abstract: Objective:Recent advances in the field of alternative medicine introduced various herbal products for the treatment of periodontitis. The purpose of this study was to evaluate the effects of combined extracts from Quercus brantii and Coriandrum sativum on periodontal indices in adult periodontitis patients.Methods:In this randomized, double-blinded clinical trial, performed in Isfahan Dental School in 2012, a new herbal medicament containing combined extracts from Q. brantii and C. sativum was formulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The sample size was estimated at 25 participants in each group based on the study of Yaghini et al, SD: 0.46, 0.63, and at least one unit of expected difference between the two groups. 9 Fifty volunteers 20‒30 years of age were selected from dental students in Shahid Beheshti School of Dentistry by a single trained periodontist (M. TA.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was estimated at 25 participants in each group based on the study of Yaghini et al, SD: 0.46, 0.63, and at least one unit of expected difference between the two groups. 9 Fifty volunteers 20‒30 years of age were selected from dental students in Shahid Beheshti School of Dentistry by a single trained periodontist (M. TA.).…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 8 In addition, bacterial accumulation in other areas of the oral cavity, such as the tongue, oral mucosa, and tonsils, can contribute to re-infection. 9 , 10 Antimicrobial mouthwashes may reduce bacterial adhesion to the tooth surfaces or the growth and division of microorganisms. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, natural products have shown many positive effects in the adjuvant therapy of periodontitis, 137–140 with the majority of them possessing exceptional anti-inflammatory, antioxidant, and bacteriostatic properties. Clinical studies 32 have shown that the subgingival delivery of 10% PEF gel as an adjunct to SRP in the treatment of chronic periodontitis can significantly improve the periodontal parameters of patients more effectively than SRP alone, including the plaque index (PI), gingival index (GI), modified sulcus bleeding index (mSBI), probing pocket dept (PPD), and clinical attachment level (CAL).…”
Section: Periodontitismentioning
confidence: 99%
“…In the research, a 4% concentration of Ocimum sanctum extract was shown to be the most efficient in combating oral bacterial microflora. In Iran, a Coriandrum sativum and Quercus brantii oral gel were recently explored (Yaghini et al, 2014). The clinical experiment used a combination of Coriandrum sativum and Quercus brantii because both plants contained tannins that may restrict bacterial activity in the periodontium.…”
Section: Role Of Medicinal Herbs In Dentistry and Tooth Regenerationmentioning
confidence: 99%